Neurological deterioration after posterior fossa decompression for adult syringomyelia: Proposal for a summarized treatment algorithm - Yuan, Chenghua; Guan, Jian; Du, Yueqi; Fang, Zeyu; Wang, Xinyu; Yao, Qingyu; Zhang, Can; Liu, Zhenlei; Wang, Kai; Duan, Wanru; Wang, Xingwen; Wang, Zuowei; et al. (Frontiers in Surgery, 2022)
Background: Patients with syringomyelia who present with new neurological symptoms after posterior fossa decompression (PFD) are not uncommon. However, systematic reports on different pathologies are few in the literature. Objective: The purpose of this study was to summarize our experience for failed PFD. Methods: Between January 2015 and December 2019, 85 consecutive failed PFD patients were identified. The neurological courses were summarized with  Klekamp J(KJ) or mJOA score system for all patients. Long-term results were summarized with Kaplan-Meier method. Results: Twenty-eight consecutive patients underwent FMDD (Foramen magnum and foramen of Magendie dredging) (Group I), extradural PFD and manipulation of tonsil was significantly associated with lower failure rates. Twenty patients underwent craniocervical fixation (Group II), nine underwent local spinal segment decompression (Group III), six underwent CSF diversion procedures, and one were treated for persistent pain by radiofrequency. Neuropathic pain was most significantly improved in Group I while swallowing improved in group II within 1 year after the surgery. In the long term, late postoperative deterioration-free possibility in Group II was better than in Group I. All patients in Group III improved (P = 0.0088). Six cases of CSF diversion procedures were relieved in a short time. Pain in one patient persisted after PFD, and trial of radiofrequency failed. Conclusion: Not only does the recurrent cerebrospinal fluid flow obstruct the foramen magnum, but also spinal pathologies and craniocervical instabilities may occur. This study provides the largest summarized clinical experience that may assist surgeons with different therapeutic decisions for failed PFD.